The Wnt/β-catenin signalling pathway in Haematological Neoplasms - Siwei Yu; Ruyue Han; Runliang Gan (BMC, 2022)
Abstract Leukaemia and lymphoma are common malignancies. The Wnt pathway is a complex network of proteins regulating cell proliferation and differentiation, as well as cancer development, and is divided into the Wnt/β-catenin signalling pathway (the canonical Wnt signalling pathway) and the noncanonical Wnt signalling pathway. The Wnt/β-catenin signalling pathway is highly conserved evolutionarily, and activation or inhibition of either of the pathways may lead to cancer development and progression. The aim of this review is to analyse the mechanisms of action of related molecules in the Wnt/β-catenin pathway in haematologic malignancies and their feasibility as therapeutic targets.